Mechanism of silica deposition in sorghum silica cells. Issue 2 (13th September 2016) - Kumar, Santosh; Milstein, Yonat; Brami, Yaniv; Elbaum, Michael; Elbaum, Rivka
Summary: Grasses take up silicic acid from soil and deposit it in their leaves as solid silica. This mineral, comprising 1–10% of the grass dry weight, improves plants' tolerance to various stresses. The mechanisms promoting stress tolerance are mostly unknown, and even the mineralization process is poorly understood. To study leaf mineralization in sorghum ( Sorghum bicolor ), we followed silica deposition in epidermal silica cells by in situ charring and air‐scanning electron microscopy. Our findings were correlated to the viability of silica cells tested by fluorescein diacetate staining. We compared our results to a sorghum mutant defective in root uptake of silicic acid. We showed that the leaf silicification in these plants is intact by detecting normal mineralization in leaves exposed to silicic acid. Silica cells were viable while condensing silicic acid into silica. The controlled mineral deposition was independent of water evapotranspiration. Fluorescence recovery after photobleaching suggested that the forming mineral conformed to the cellulosic cell wall, leaving the cytoplasm well connected to neighboring cells. As the silicified wall thickened, the functional cytoplasm shrunk into a very small space. These results imply that leaf silica deposition is an active, physiologically regulated process as opposed to a simple precipitation.